2017
DOI: 10.7863/ultra.16.05073
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-Care Ultrasound Use, Accuracy, and Impact on Clinical Decision Making in Rwanda Hospitals

Abstract: A point-of-care ultrasound training intervention in a low-resource setting resulted in high numbers of diagnostic-quality studies over long-term follow-up. Ultrasound use routinely changed clinical decision making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 14 publications
1
57
0
Order By: Relevance
“…POCUS is becoming standard of care for diagnostic and therapeutic interventions in a variety of clinical settings in highly developed medical systems (Bellamkonda et al 2015;Dietrich et al 2017;McLario and Sivitz 2015;Moore and Copel 2011). In recent years there has been an increasing effort to integrate POCUS into clinical care provided in resource-limited settings (Becker et al 2017;B elard et al 2018;Epstein et al 2018;Henwood et al 2017;Stanley et al 2017;Vinayak 2017;Vinayak and Brownie 2018;Zaver et al 2018). These efforts include initiatives to improve the relevance of ultrasound training programs enabling clinicians with a point-of care imaging modality.…”
Section: Introductionmentioning
confidence: 99%
“…POCUS is becoming standard of care for diagnostic and therapeutic interventions in a variety of clinical settings in highly developed medical systems (Bellamkonda et al 2015;Dietrich et al 2017;McLario and Sivitz 2015;Moore and Copel 2011). In recent years there has been an increasing effort to integrate POCUS into clinical care provided in resource-limited settings (Becker et al 2017;B elard et al 2018;Epstein et al 2018;Henwood et al 2017;Stanley et al 2017;Vinayak 2017;Vinayak and Brownie 2018;Zaver et al 2018). These efforts include initiatives to improve the relevance of ultrasound training programs enabling clinicians with a point-of care imaging modality.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a study in Kenya demonstrated the utility of a focused cardiac protocol applied in patient care by clinical officers [54]. Henwood et al also demonstrated that a longitudinal ultrasound training program could detect basic cardiac abnormalities with high sensitivity and specificity when compared to experienced sonographer interpretation [55]. These studies suggest that implementation of a focused CURLS protocol is feasible.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to provide US imaging in resource‐limited environments can provide a unique perspective to medical providers and vastly improve their access to critical information for the medical decision‐making process . Ultrasound in developing countries has proved to be effective in obstetrics, trauma, cardiac and surgical emergencies, and procedural guidance, coupled with the fact that medical professionals have been successful in implementing programs in developing countries to train providers with limited medical training to conduct US scans . Perhaps with the introduction of DL models, these capabilities can be expanded even further.…”
Section: Deep‐learning Applications In Pocus Practicesmentioning
confidence: 99%